An Otago Storeman in Solomon Islands: The diary of William Crossan, copra trader, 1885-86 - Bayliss-Smith, Tim (ANU Press, 2012)
An Otago Storeman in Solomon Islands reaches from inland South Island of New Zealand across to the Solomon Islands during the 1880s. William Crossan's Otago experience as a versatile storeman with a solid work ethic helped him survive on the Melanesian frontier where he encountered conflicting clans, cannibalism, cheating traders, and co-operative entrepreneurial big men. His diary provides many glimpses into Makiran society as it encountered new ideas, new employment, and western technology. It is a welcome addition to the sparse record of these cryptic copra traders seeking fortunes on the cusp of indigenous tradition and incoming colonialism.